(untitled) (KYAMC Journal, 2025)
Hypokalemia is common in clinical practice. But severe hypokalemia can cause rhabdomyolysis followed by AKI. Rhabdomyolysis is the breakdown of skeletal muscle fibers with leakage of muscle contents into circulation. Hypokalemia-induced rhabdomyolysis is a result of skeletal muscle hypoperfusion leading to ischemia. Acute kidney injury is a potential complication of severe rhabdomyolysis and it can be life-threatening. KYAMC Journal Vol. 15, No. 04, January 2025: 199-200